Effect of Training on Job Performance: A Case of Nepalese Civil Servants - Niraula, Ganesh Pd.; Niroula, Ballav (Patan Prospective Journal, 2022)
This research aims to find out the effect of training on the performance of Nepalese civil servants. This research follows a survey research method. It provides a brief analysis and an understanding of the job performance of Nepalese civil servants. The total population of this study is 88657 (65089 males and 23568 females) and 116 samples have been taken for this study. The simple random sampling technique has been applied for the selection of the respondents. The primary data collected through structured questionnaires are analyzed and interpreted using descriptive and inferential statistics. This study's findings revealed on the job performance of civil servants in Nepal. The independent variables (learning, good governance, e-governance and motivation). The dependent variable is the job performance of civil servants. It is revealed that the training has played a crucial role in the job performance of Nepalese civil servants through the utilization of learning, motivation, and good governance and E-governance mechanism. The results show, there is a positive and significant effect of motivation, E-governance, and good governance but learning has a negative and insignificant effect on job performance of Nepalese civil servants.